A Proton Leak Current through the Cardiac Sodium Channel Is Linked to Mixed Arrhythmia and the Dilated Cardiomyopathy Phenotype - Gosselin-Badaroudine, Pascal (Public Library of Science, 2012)
Cardiac Na(+) channels encoded by the SCN5A gene are essential for initiating heart beats and maintaining a regular heart rhythm. Mutations in these channels have recently been associated with atrial fibrillation, ventricular arrhythmias, conduction disorders, and dilated cardiomyopathy (DCM). We investigated a young male patient with a mixed phenotype composed of documented conduction disorder, atrial flutter, and ventricular tachycardia associated with DCM. Further family screening revealed DCM in the patient's mother and sister and in three of the mother's sisters. Because of the complex clinical phenotypes, we screened SCN5A and identified a novel mutation, R219H, which is located on a highly conserved region on the fourth helix of the voltage sensor domain of Na(v)1.5. Three family members with DCM carried the R219H mutation. The wild-type (WT) and mutant Na(+) channels were expressed in a heterologous expression system, and intracellular pH (pHi) was measured using a pH-sensitive electrode. The biophysical characterization of the mutant channel revealed an unexpected selective proton leak with no effect on its biophysical properties. The H(+) leak through the mutated Na(v)1.5 channel was not related to the Na(+) permeation pathway but occurred through an alternative pore, most probably a proton wire on the voltage sensor domain. We propose that acidification of cardiac myocytes and/or downstream events may cause the DCM phenotype and other electrical problems in affected family members. The identification of this clinically significant H(+) leak may lead to the development of more targeted treatments.